Introducing New Modes of Organizational Collaboration: A Change Management Perspective (European Journal of Marketing and Economics, 2023)
This publication deals with the specific challenges that can arise when introducing remote and hybrid working conditions in companies. A comparison is made with the implementation of agile management methods, which were investigated accordingly within the framework of an empirical-qualitative study. In the context of the examination of the state of research, the problems that arise both in the implementation and the actual use of hybrid and remote working methods are presented. Agile leadership is described here on the one hand as a potential solution to communicative problems and on the other hand it is shown how the introduction of such a leadership approach coincides with that of remote and hybrid leadership with regard to its problem specifics and potential solutions. A series of recommendations for managers is derived, which should enable them to successfully manage the war for talent in a working environment characterised by hybrid working methods.
Keywords: remote, hybrid, agile, leadership, modes, work